2001
DOI: 10.1161/hc3701.095949
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell Adhesion Molecules and Death in Patients With Coronary Artery Disease

Abstract: MD; for the AtheroGene InvestigatorsBackground-Vascular cell adhesion molecule (VCAM)-1, intercellular adhesion molecule (ICAM)-1, and E-selectin mediate adhesion and transmigration of leukocytes to the vascular endothelial wall and may promote plaque growth and instability. In a prospective study, we evaluated the effect of soluble adhesion molecules on the risk of future cardiovascular events among patients with angiographically documented coronary artery disease (CAD). Methods and Results-We obtained baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
366
2
27

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(412 citation statements)
references
References 22 publications
17
366
2
27
Order By: Relevance
“…6 Other inflammatory biomarkers, such as high-sensitivity C-reactive protein, soluble intercellular adhesion molecule, soluble vascular cell adhesion molecule or interleukin-6 did not correlate with endothelial function in this group of patients. Although they are also produced totally or partially in the endothelium, and they have been found increased in hypertension 13,14 or in patients with cardiovascular disease, 21 no clear relationship with the endothelial function was observed in this study. A possible explanation of this different behaviour could be found in the relative young age of the study population, which was recently diagnosed of essential hypertension and was free from overt cardiovascular disease.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…6 Other inflammatory biomarkers, such as high-sensitivity C-reactive protein, soluble intercellular adhesion molecule, soluble vascular cell adhesion molecule or interleukin-6 did not correlate with endothelial function in this group of patients. Although they are also produced totally or partially in the endothelium, and they have been found increased in hypertension 13,14 or in patients with cardiovascular disease, 21 no clear relationship with the endothelial function was observed in this study. A possible explanation of this different behaviour could be found in the relative young age of the study population, which was recently diagnosed of essential hypertension and was free from overt cardiovascular disease.…”
Section: Discussioncontrasting
confidence: 77%
“…30 They have all been related to the risk of future cardiovascular events in healthy women 31 and especially in patients with coronary artery disease. 21,22 We have previously reported increased levels of these biomarkers in salt-sensitive hypertensive patients, 25 irrespective of the level of salt intake, a group also characterized by a more impaired endothelial function. 6 Other inflammatory biomarkers, such as high-sensitivity C-reactive protein, soluble intercellular adhesion molecule, soluble vascular cell adhesion molecule or interleukin-6 did not correlate with endothelial function in this group of patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…47,48 Elevated CRP levels have also been found to significantly correlate with vascular ED as measured by penile Doppler. 49 Finally, markers of cellular adhesion, such as E-selectin, 50 intercellular adhesion molecule-1 Assessment of endothelial function in men with ED R Tamler and N Bar-Chama (ICAM-1) 44,51 or vascular cell adhesion molecule-1 (VCAM-1) 46 and thrombogenesis, such as von Willebrand factor (vWF) 52 or plasminogen-activator inhibitor type-1 (PAI-1) 53 have also been associated with endothelial dysfunction and increased risk of CAD. 54 This underlines the importance of inflammation and cellular adhesion in early atherosclerosis, 55 but-with the exception of CRP-so far has not resulted in increased clinical usability.…”
Section: Serum Markersmentioning
confidence: 99%
“…This association was independent of other risk factors, including the nonspecific inflammatory indicator C-reactive protein, and, in a multivariable model, sVCAM-1 was the only independently predictive soluble cell adhesion molecule. 45 Several authors [46][47][48][49] have reported increased levels of sICAM-1 and sVCAM-1 in cohorts with unstable coronary heart disease. Nevertheless, subtle differences are once again apparent.…”
Section: Soluble Icam-1 and Vcam-1 As Prognostic Markersmentioning
confidence: 99%